An Assessment of Environmental Education Awareness, Attitudes and Engagements for Environmental Sustainability in Nigeria: A Case Study of LAUTECH Students - MORAKINYO, Oladotun Ebenezer; TAIWO, Richard Oluseyi; MORENIKEJI, Timothy; ABDULQUADRI, Khadijat; OYENIYI, Samuel Ayobami; OYENIRAN, Demilade Oyewumi; YUSUFF, Iskil Olatunde; ODOH, Augustine Eje (ABUAD Journal of Engineering and Applied Sciences, 2025)
Environmental sustainability necessitates awareness, an attitude regarding oneself and the environment, along with proper conduct and ethical values, which Environmental Education (EE) provides. Therefore, EE is critical in developing countries such as Nigeria, which are confronted by significant environmental problems such as deteriorating ecosystems, erosion, flooding, loss of biodiversity, and climate change. Because the ability to handle environmental challenges depends heavily on the young, as it is easiest to attain greater consciousness among them, this study assessed students’ EE exposure and awareness, knowledge of environmental problems, attitude and perceptions towards environmental sustainability, engagement to promote environmental sustainability and barriers to engagement. Using a questionnaire survey and convenience sampling, this study sampled 300 LAUTECH students from various academic disciplines, levels and demographic backgrounds. The collected data were analysed using IBM SPSS to generate descriptive statistics such as frequency, percentage and mean. The findings revealed that most of the respondents have heard of EE (4.19), primarily through informal education (3.77). Also, the environmental problems the respondents are mostly familiar with are pollution and waste management problems (4.22). While the students are highly interested in pursuing actions that promote environmental sustainability, they are constrained by restricted access to information on environmental issues (3.46) and organisations that promote environmental sustainability in Nigeria (3.24). The study recommended that Education for Sustainable Development, which includes EE and sustainability topics, should be incorporated into core subjects of the National Education Curriculum in Nigeria. Also, EE should be intensified formally and promoted informally through online sources, study groups, environmental clubs and partnerships with environmental NGOs.